Hubungan Tingkat Pengetahuan Ibu Tentang MP-ASI Dengan Kejadian Stunting Pada Anak Usia 2-5 Tahun Di Kecamatan Tapa Bone Bolango - Adjid, Asyulni Almaida; Haji Jafar, Cindy Puspita Sari; Mohamad, Rini Wahyuni (PT.Mantaya Idea Batara, 2024)
Nutrient-rich meals and drinks are provided to babies and as an addition to breast milk for children six to twenty-four months old to help them meet their dietary requirements. Finding out how frequent stunting is among kids in the Tapa SubDistrict between the ages of two and five is the aim of this study. Bone Bolango and the degree of supplementary feeding knowledge among mothers. This crosssectional design is used in this analytical observational quantitative investigation. Purposive sampling strategies were employed in this study to choose women from Tapa Sub-District, Bone Bolango, who had stunted children aged two to five years. The Spearmen Rank (Rho) test is then used to examine the collected data. The research findings revealed that, of the respondents, 24 (60.0%) had sufficient knowledge, 14 (35.5%) had poor knowledge, and 2 (5.0%) had good knowledge. Stunting was reported to occur in 28 (70.0%) children in the stunting category and 12 (30.0%) in the very short group. The conclusion of this research is that there is a significant relationship between the level of maternal knowledge about MP-ASI and the incidence of stunting in children aged 2-5 years in Tapa District with a p value of 0.000 (<0.05) with a correlation of 0.543 with strong correlation strength.